Association of systemic inflammation index with survival in patients with advanced perihilar cholangiocarcinoma treated with interventional therapy - Li, Jinyu; Gao, Long; Liu, Tianci; Feng, Duiping (Frontiers in Oncology, 2022)
Immunity and inflammation are key mediators of carcinoma development, invasion and metastasis. However, it remains unknown whether the systemic immune-inflammation index (SII) can be used as a prognostic indicator for cholangiocarcinoma. In this study, we investigated the association and predictive value of the SII with the prognosis of advanced perihilar cholangiocarcinoma (pCCA) after interventional therapy. A retrospective cohort of patients with advanced pCCA treated with interventional therapy at the First Hospital of Shanxi Medical University enrolled in this study from January 2019 through January 2021 was examined. Cox regression models were used to analyze the relationship between the SII and overall survival (OS) of patients with advanced pCCA. Receiver operating characteristic (ROC) analysis was used to evaluate the predictive power of SII. The median OS of the 66 patients was 257.0 days. Preoperative SII was positively associated with poor OS of pCCA after interventional therapy, with corresponding hazard ratios (HR) of 1.57 (95% CI: 1.17 - 2.10) for an inter-quartile range increase. The predictive power of SII was higher than that of other inflammation indexes based on ROC analysis (AUC = 0.835 [95% CI (0.731 - 0.940)]). The optimal cut-off values, sensitivity, and specificity with SII were 700, 0.774 and 0.846, respectively. An SII ≥ 700 was significantly associated with lymph node metastasis and high carbohydrate antigen199 (CA199) level. In multivariate analyses, total bilirubin, carbohydrate antigen 199, vascular invasion, and SII independently predicted overall survival (P < 0.05). This is the first study demonstrating that an increase in the SII is associated with poor advanced pCCA prognosis, and could serve as a reliable prognostic indicator of pCCA after interventional therapy.